Purificação, caracterização bioquímica e biológica e especificidade fina da lectina galactose-específica (VGL) de sementes de Vatairea guianensis Aublet - Isidro, Renato (2002)
Biochemical aspects and fine specificity of the lectin from seeds of Vaitarea guianensis Aublet were analysed in the present work. The purified lectin obtained by affinity chromatography on Guar-Gum column was used to study both structural parameters and its specificity to bind to complex carbohydrates and glycoconjugates. Furtherrnore, the ability of the lectin to recognize glycoconjugates from the surface of different ceU tines of human colon cancer was also investigated. In a view to characterise the binding specificity of the lectin to carbohydrates, a large amount of soluble carbohydrates and glycoproteins were used to abolish the haemagglutinating activity exhibited by the lectin. Also, the affinity of the immobilized lectin into Sepharose 4B against radiolabeled oligossacharides and glycopeptides marked with 14Cor 3H of well-defined structures was determined. The kinetic interaction in real time of soluble VGL with various immobilized glycoproteins was analysed by surface plasmon resonance technology in a BIACore 3000™ apparatus. In general, VGL is formed by a mixture of both intact subunits (n-chain) and cleaved units (P and À.), containing an expressive amount of a galactose/lactose-specifíc lectin. VGL was partially recognized by rabbit polyclonal antibodies anti-VML by ELISA assay. PAGE-SDS, mass spectrum and ELISA data suggested that VGL might have similar structural relationships lea ing to similar biological activities. VGL is a glycoprotein with 3.6% sugar content, with one fucose, three mannose, two N-Acetyl-glycosarnine and one xylose residues per molecule. This glycan structure occurs in a large amount of plant proteins. Haemagglutination inhibition studies showed that the simple sugars fucose, glucose, N-acetyl-glucosamine, mannose and its derivatives did not abolish the agglutinatining activity exhibited by the lectin. However, lactose, galactose and its derivative N-acetyl-galactosamine showed to be inhibitors of the haemagglutinanting activity. The interaction of the lectin with several glycoproteins, measured by haemagglutinating activity showed that the lectin recognized galactose and Ncetyl- galactosamine residues into the core of the glycoproteins asialofetuin, human asialolactotransferrin, human asialo-sorotransferrin and bovine lactotransferrin. However, fine specificity studies by affinity chromatography showed that immobilized VGL recognizes some N-acetyl-lactosarnine B-Gal-(1-4)-B-GlcNAc type exhibiting two, three or four antennas since they were eluted after the void volume (FR+ 1). The kinetic interaction of the lectin with several glycoproteins in real time has shown that VGL possesses different affinity for the glycan structures. The results suggested that VGL exhibits similar characteristics to the lectin isolated from the seeds of Vatairea macrocarpa and that they probably evaluated from a common ancestor. Flux cytometry rcsults revealed that both lectins isolated from seeds of genus Vaitarea used in the present work recognized in different intensit some carbohydrate moieties in ali line of cells tested. However, VML exhibited more specificity to distinguish the cell lines since it exhibited more affinity for the glycans presented in the surface of the celI lines by the values of Fluorescence Units (FU) detected. As both lectins from genus Vaitarea appears not to bind to complex carbohydrates that possess sialic acid in their structure, make them an useful tool for the study and detection of N-acetyl-lactosamine type-glycoconjugates that have or not sialic acid residues in non-reducing extremity.